2016
DOI: 10.1111/jav.00936
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in winter supplementary food consumption and its consequences for reproduction in wild birds

Abstract: The provision of wild birds with supplementary food has increased substantially over recent decades. While it is assumed that provisioning birds is beneficial, supplementary feeding can have detrimental 'carry-over' effects on reproductive traits. Due to difficulties in monitoring individual feeding behaviour, assessing how individuals within a population vary in their exploitation of supplementary food resources has been limited. Quantifying individual consumption of supplementary food is necessary to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 60 publications
(86 reference statements)
1
41
0
1
Order By: Relevance
“…R 2 (CONDITIONAL) -R 2 (MARGINAL) gives the random effect component of the variance, R 2 (RANDOM) . R 2 (RANDOM) is analogous to repeatability (Nakagawa and Schielzeth, 2010;Crates et al, 2016). Note, estimating the variance components of fixed vs. random effects for negative binomial models required refitting models using the "glmmPQL" function of the MASS package (which uses penalized quasilikelihood for parameter estimation; Venables and Ripley, 2002), as glmmADMB objects cannot be passed to "r.squaredGLMM."…”
Section: Individual Visitation (Pit-tag Data)mentioning
confidence: 99%
See 2 more Smart Citations
“…R 2 (CONDITIONAL) -R 2 (MARGINAL) gives the random effect component of the variance, R 2 (RANDOM) . R 2 (RANDOM) is analogous to repeatability (Nakagawa and Schielzeth, 2010;Crates et al, 2016). Note, estimating the variance components of fixed vs. random effects for negative binomial models required refitting models using the "glmmPQL" function of the MASS package (which uses penalized quasilikelihood for parameter estimation; Venables and Ripley, 2002), as glmmADMB objects cannot be passed to "r.squaredGLMM."…”
Section: Individual Visitation (Pit-tag Data)mentioning
confidence: 99%
“…in woodland habitat in Oxford, UK, during winter (Crates et al, 2016) and the other examining visitation patterns of six species at a university campus in Cornwall, UK (Jack, 2016). These studies both reported individual and interspecific variation in use of supplementary food at experimental feeders over a comparatively shorter timeframe (c. 3 months).…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on our population showed that the number of visits to feeders over the whole winter has no effect on these measures of fitness (Crates et al . ), but the fitness consequences of alterative foraging tactics were not explored. Variation in the timing of feeding is also likely to be caused by differences in physiological state and the environment, so it will be important to investigate the effects of condition, perceived predation risk, temperature and flock structure in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…As such, recent research has begun to investigate the consequences of winter supplementary feeding on subsequent avian productivity, reporting both beneficial (Robb et al., ) and detrimental effects on breeding performance at the population level (Plummer, Bearhop, Leech, Chamberlain, & Blount, ,b). It has been assumed that such carry‐over effects are mediated via the impacts of winter supplementary food on overwinter survival and/or on avian condition during the breeding season (Brittingham & Temple, ; Crates et al., ; Gosler, ; Plummer et al., ; Robb et al., ), although this remains to be studied in detail. Given the enormity of anthropogenic bird feeding activities, and as provisioning of food for wild birds is often advocated as a method for conserving declining populations (Ewen, Walker, Canessa, & Groombridge, ; Jones & Reynolds, ; RSPB, ), it is imperative that the mechanisms driving any negative carry‐over effects of winter feeding are investigated.…”
Section: Introductionmentioning
confidence: 99%